2010
DOI: 10.3844/ajassp.2010.459.465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cycocel and Irrigation Regimes on Some Physiological Parameters of Three Olive Cultivars

Abstract: Problem statement:The water deficiency is one of the serious problems, in the arid zones. Cycocel by increasing the stomata resistance and decreasing transpiration can help to water use efficiency. Approach: In this research the impacts of different doses of Cycocel (0, 500 and 1000 mg L ) and irrigation regimes (33, 66 and 100% of available water; referred to as I 1 , I 2 and I 3 , respectively) on some physiological parameters of three olive cultivars (Baghmalek, Fishami and Dezfuli) were investigated. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The shortage of water, i.e., drought, during the crop growing period inhibits the chlorophyll a (Chl a) & chlorophyll b (Chl b) synthesis, and decreases the quantity of Chl a & Chl b binding proteins, ultimately reducing the light-harvesting pigment protein which is linked with photosystem II [18]. Moreover, under this condition, the concentration of solutes in the soil increases, which reduces the access of the roots, thereby decreasing water reception by the roots, and consequently declining the leaf water potential [19].…”
Section: Introductionmentioning
confidence: 99%
“…The shortage of water, i.e., drought, during the crop growing period inhibits the chlorophyll a (Chl a) & chlorophyll b (Chl b) synthesis, and decreases the quantity of Chl a & Chl b binding proteins, ultimately reducing the light-harvesting pigment protein which is linked with photosystem II [18]. Moreover, under this condition, the concentration of solutes in the soil increases, which reduces the access of the roots, thereby decreasing water reception by the roots, and consequently declining the leaf water potential [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hoque and Haque (2002) reported that CCC prevents ent-kaurene synthesis in the GA 3 biosynthetic cycle leading to GA 3 deficiency and the subsequent reduced vegetative growth potential. Nejadsahebi et al (2010) reported that the application of CCC in water limitation, increased RWC and stomata resistance. Wang and Xiao (2009) imply that treatment of plants with CCC may increase the number of chloroplasts, elevate the concentration of chlorophyll and carotenoids, accelerate the process of photophosphorylation, and stimulate the photosynthetic rate.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of proline is known to function in osmotic adjustment, protection of cellular macromolecules from damage by salts, storage of nitrogen and scavenging of free radicals which is supported by Chookhampaeng et al (2008) [4] . (2010) [9] .…”
Section: Physiological Parameters Proline Contentmentioning
confidence: 99%